Partikel fatis dalam bahasa Mandarin; Sebuah telaah awal - Sutami, Hermina (Wacana, Journal of the Humanities of Indonesia, 2005)
Phatic particles are rarely discussed, especially in the scope of syntax, even though the notion of phatic communion had been proposed by Malinowski in 1923. In Indonesian language, Harimurti (1986) had pioneered the inclusion of phatic expression into the Indonesian parts of speech. In Mandarin language, there has not been any special interest to discuss it. Generally phatic particles overlap with interjections and interrogatives. However, this article discusses about some evidences about the differences among them.